ANALISIS PERENCANAAN PENAMBAHAN TEMPAT HENTI TRANS JOGJA (STUDI KASUS: PELAJAR DAN MAHASISWA DI WILAYAH AGLOMERASI PERKOTAAN YOGYAKARTA) - Puput Budy Aryanti; Siti Malkhamah; Sigit Priyanto (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2020)
The use of private vehicles that are increasingly out of control causing traffic congestion. About 71% students and college students in the city of Yogyakarta use private vehicles daily. The main solution to overcome this in Yogyakarta is by improving the quality of public transportation. Students are reluctant to use public transportation because their residential area is not yet reached by Trans Jogja. The purpose of this study is to analyze the need to add bus stops that are suitable for students in the Urban Aglomeration Area of Yogyakarta in order to increase the student's desire to use Trans Jogja, so that it is expected to reduce congestion. The results of this study indicate that the distance between the school or campus to a bus stop has already met the standard, but there are still as many as 9% of students whose school or campus's location is within >400 meters to the bus stop. Meanwhile, the distance from the house to the bus stops does not meet the standards because as many as 45% of students whose house location is within > 400 meters to the bus stop. So Trans Jogja need to add additional stops around residential houses and around schools or campuses to increase the number of students to use Trans Jogja as many as 330 bus stop points consisting of 267 existing bus stops and 63 new bus stops. Keywords: trans jogja, bus stop, public transportation